Size Matters in Turkish Higher Education - Esen, Oğuz (International Higher Education, 2020)
In recent years, mergers and consolidation have been widely used in higher education to create stronger, more competitive universities in the transition from mass to universal access. In Turkey, however, developments have gone in the opposite direction. Initially, a number of smaller-scale, highly specialized public universities were founded, and recently new universities were established by splitting larger-scale, existing universities. Universal access requires a more comprehensive vision.